(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the meaning and essence of the concept, signs, classification and characteristics of crimes in the field of economy, methods of committing these types of crimes, reasons and conditions that make it possible, evidence, the importance of evidence in exposing these types of crimes and in the process of proving them problems and their solutions are studied according to their specific characteristics.